The Evaluation of Lecturer's Performance and Sekolah Tinggi Perikanan's Performance Through Intellectual Capital - Aida VitayalaS. Hubeis, Mextaria Yuliana, Anggraini Sukmawati, (Jurnal Manajemen, 2019)
Intellectual capital is an intangible resource owned by the organization that can be used to create value for the organization. Intellectual capital consists of the source of human capital, the organization itself and its relationship to the environment. The purpose of this research is to analyze the effect of intellectual capital on lecturer and organizational performance and the effect of lecturer performance on organizational performance. Lecturer performance was measured by Key Performance Indicator value. Organizational performance was measured by perspective of costumer, finance, internal business process, learning and growth. Respondents of this research were 106 lecturers in Sekolah Tinggi Perikanan. Data was analyzed by descriptive analysis and Structural Equation Modeling (SEM) with LISREL. The results showed that intellectual capital has positive effect and significant on lecturer and organizational performance. Lecturer performance has positive effect on organizational performance, but insignificant. University is the organization which high intellectual capital, so organization could be able to manage them for improving performance.